Family language policy and Chinese-English bilingualism: an exploratory study of Beijing families - Wang, C; Chalmers, H (2022)
Family language policy (FLP) studies language ideology, management, and practice among family members in the home domain. Although English is a global lingua franca and the fever for English learning has persisted in China for decades, there has been little research on how mainland Chinese parents perceive, manage, and practice English language learning and use for their children. This study aims to learn how some Chinese parents perceive Chinese-English bilingualism, manage English learning for their children, and practice English use with their children. With a mixed methods design, this study recruited 26 parents of primary school children in Beijing for the questionnaire and three of the 26 parents for the semi-structured interview. The children (aged 6 to 12) went to a Chinese monolingual primary school where they learned English as a foreign language (EFL). Results show that the parents had highly positive attitudes toward their children’s Chinese-English bilingual development, but they were unable to communicate with their children in English at home due to their limited English proficiency. As a result, the parents sought alternative methods to help develop and improve their children’s English skills. The findings reveal an ideology-practice gap among these Beijing parents and significant barriers to parent-child communication in English at home.